(untitled) - Sell, Stewart (Washington, D.C., 2001)
A systematic account of the effects, both good and bad, of the immune system. • Covers what the immune system actually does in causing and preventing disease. • Discusses inflammation, the fundamentals of the immune system and how it is activated, the seven immune effector mechanisms, and how these effector mechanisms act not only to protect against infection and cancer but also to cause diseases. • Serves as a resource for physicians, medical students, graduate students, nurse practitioners, physician assistants, teachers of immunology, and advanced courses in immunology.
Keywords: Immune System,Hệ thống miễn dịch; Physiopathology,Sinh bệnh học